Abdullah Nashih ‘Ulwan’s Technological Contribution toward the Development of Islamic Early Childhood Education - Purnama, Sigit (Jurnal Pendidikan Islam, 2018)
The development of science and technology has an impact on the use of technology in education. The application of educational technology in learning is aimed at creating more effective, efficient, and meaningful learning for children. Meanwhile, Islam, which is revealed as a paradigm, explains that education is the best way in developing human nature as well as human resources towards the formation of ‘Insan Kamil’. One of the notable Moslem thinkers worthen to be discussed in this case study is Abdullah Nashih 'Ulwan who has written a monumental work in education entitled ‘Tarbiyatul Aulad fil Islam’. This study sought answers to Ulwan's contributions to the development of early childhood education. The results of this study show that Ulwan's thought cannot be separated from a particular movement namely ‘Ikhwanul Muslimin’. The critical foundation of Ulwan's thinking on child education is essentially derived from his thinking about fitrah. Fitrah, according to ‘Ulwan, is a nature in which humans have a tendency of innate good and evil. Therefore, children at their early age require particular forms of conditioning to develop learners’ type of personality through three approaches namely: the formulation of appropriate child education methods, the establishment of educator readiness and attachment to children, and the conditioning of early childhood education environments.